2007
DOI: 10.1002/hbm.20460
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neural activity associated with learning to articulate novel auditory pseudowords by covert repetition

Abstract: Learning to articulate novel combinations of phonemes that form new words through a small number of auditory exposures is crucial for development of language and our capacity for fluent speech, yet the underlying neural mechanisms are largely unknown. We used functional magnetic resonance imaging to reveal repetition-suppression effects accompanying such learning and reflecting discrete changes in brain activity due to stimulus-specific fine-tuning of neural representations. In an event-related design, subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
69
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 83 publications
11
69
1
Order By: Relevance
“…The IFG/IPL was less implicated in triggering the parieto-somato-motor network, whereas the STG/PM increased its driving force. This is testified by the connection that all components of the parieto-somato-motor network receive from the primary IC and is further corroborated by previous studies [Newman and Twieg, 2001;Rauschecker et al, 2008]. The processing of meaningless stimuli can only rely on bottom-up, sound-based analysis, sustained for longer times [Roy et al, 2008].…”
Section: Second-order Connectivitysupporting
confidence: 66%
“…The IFG/IPL was less implicated in triggering the parieto-somato-motor network, whereas the STG/PM increased its driving force. This is testified by the connection that all components of the parieto-somato-motor network receive from the primary IC and is further corroborated by previous studies [Newman and Twieg, 2001;Rauschecker et al, 2008]. The processing of meaningless stimuli can only rely on bottom-up, sound-based analysis, sustained for longer times [Roy et al, 2008].…”
Section: Second-order Connectivitysupporting
confidence: 66%
“…Both regions are established contributors to speech production (Bohland & Guenther, 2006;Brendel et al, 2010;MacNeilage, 2008;Peeva et al, 2010;Penfield & Welch, 1951) but are nonetheless observed during purely receptive phonological working memory tasks (e.g., Awh et al, 1996;Rauschecker, Pringle, & Watkins, 2008;Strand et al, 2008). Both of these regions exhibited scaling response with increasing phonological working memory load in the present study as well, despite the purely receptive nature of the phonological working memory task.…”
Section: Phonological Working Memory Beyond Left Stgsupporting
confidence: 43%
“…The PMv activated during preferred rhythms and tempo and its adjacent areas, the inferior frontal gyrus and the Rolandic operculum, have been shown to be involved in voice-related tasks, such as singing [Ozdemir et al, 2006;Perry et al, 1999] and speech [Wildgruber et al, 1996], as well as singing imagery [Kleber et al, 2007;Riecker et al, 2000] and speech imagery [Rauschecker et al, 2008;Shergill et al, 2006]. The premotor activation we found most likely overlaps with the precentral area crucial for the control of learned vocal patterns, e.g.…”
Section: Discussionmentioning
confidence: 65%
“…Second, a motor imagery explanation cannot be reconciled with the absence of activation in dorsal premotor regions for neck and foot movements. And thirdly, there was no activity increase in areas characteristic for motor imagery and motor preparation such as the primary motor cortex, primary and secondary somatosensory areas, and especially the SMA/pre-SMA, an area which has been shown to be most reliably involved in vocal imagery [Kawashima et al, 2000;Kleber et al, 2007;Rauschecker et al, 2008;Riecker et al, 2000;Thobois et al, 2000]. Thus, it seems more consistent with the data to consider premotor involvement during preferred rhythms and tempo as an audiomotor fraction of vocal and articulatory representations that are exploited during attention to external rhythmic events.…”
Section: Discussionmentioning
confidence: 99%